IMPLEMENTATION OF INTEGRATED QUALITY MANAGEMENT FOR QUALITY EDUCATION AMIDST DYNAMIC CHANGES - Khoirun Nisa'; Maryani, Maryani; Oktaviana Nur Handayani; Raykes Hinrich Tuerah (Penerbit Lafadz Jaya, 2025)
Education in Indonesia is undergoing significant transformation influenced by technological advances, policy changes, and the challenges of globalization. This article discusses the role of Total Quality Management (TQM) as a strategic approach to improving the quality of education, while also addressing the challenges faced by the national education sector. The purpose of this study is to explore the application of TQM in creating quality education through continuous improvement, stakeholder engagement, and strong leadership. This study uses a literature review method to analyze various relevant references. The results of the study indicate that TQM contributes to improving the quality of education through the integration of the principles of planning, implementation, evaluation, and continuous improvement. TQM also facilitates the active involvement of all stakeholders, including educators, students, and the community, to promote a culture of quality. In addition, the application of technology in education is recognized for its potential in improving the effectiveness of learning and administration. The successful implementation of TQM requires adequate infrastructure, continuous training for teachers, and policies that support educational equality and innovation. This implementation is expected to be able to create a globally competitive education system, producing innovative and highly competitive graduates.